Dimeric complexes of transition metal based on azole nucleating ligands involving hydrogen bonding interactions. (5th September 2016) - Feng, Chao; Zhang, Duo; Chu, Zhao-Jing; Zhao, Hong
Graphical abstract: Three dimeric complexes were demonstrated in this work. In order to investigated the intermolecular interactions, Hirshfeld surface analysis was carried out on the title complexes. Abstract: Self-assembly through tuning the N -donor azole ligands and coordinative preferences of transition metal Cu(II), Cd(II) and Co(II) ions, three dimeric complexes, namely [Cu2 (Hmpz)4 ( μ 2 -Cl)2 Cl2 ] (1 ), [Cd2 (pmtz)2 Cl2 (H2 O)4 ] (2 ) and [Co2 (Hmptz)2 Cl2 (H2 O)4 ]Cl2 ·H2 O (3 ) have been synthesized at solvent method and hydrothermal conditions and characterized by single crystal X-ray diffraction analyses and fluorescent property were investigated, where Hmpz = 3-methyl-1 H -pyrazole, Hpmtz = 5-methyl-1-phenyl-1 H -1, 2, 3-triazole-4-carboxylic acid, and H2 mpta = 5-methyl-1-(1 H -pyrazol-3-yl)-1 H -1, 2, 3-triazole-4-carboxylic acid, respectively. In order to investigate the intermolecular contacts, Hirshfeld surface was studied in this work. The Hirshfeld surface analysis was successfully deployed here to visualize and elaborate the similarities and differences in the molecular environments of the three complexes.